THE OUTCOME OF COGNITIVE THERAPY IN PATIENTS WITH FIRST-EVER STROKE AND RECURRENT STROKE - Rianawati, Sri Budhi; Wardani, Rachmawati (MNJ (Malang Neurology Journal), 2024)
Background: Vascular dementia (VaD) is the second most prevalent type of dementia that impacts elderly adults, succeeding Alzheimer's disease. In contrast to Alzheimer's disease, Vascular Dementia (VaD) presents a wide range of cognitive changes, which are greatly influenced by the specific neural regions that are impacted by vascular pathology. The incidence of dementia in adults with a prior history of stroke is 30%, demonstrating a frequency that is 3-5 times more than those without any discernible stroke-related impairments. In addition, the intensity or frequency of strokes may contribute to a decrease in cognitive reserve in persons with vascular dementia. Case Report: We presented two cases of VaD. The first case was a 62-year-old man with a history of ischemic stroke without sequelae a year before the complaints of frequent forgetfulness and cognitive impairment. Neuropsychological examination showed neurocognitive disturbances in orientation, attention, memory, and visuospatial domain with impaired daily activities function. The MRI result showed senile brain atrophy with chronic infarction on the right temporoparietooccipital lobe, left side mesencephalon, right side pons accompanied by cortical laminar necrosis on the right frontal lobe and left temporoparietal lobe. The second case was a 79-year-old man with history of recurrent ischemic stroke (three times since 2021-2022) with sequelae of left hemiparesis and complaints of frequent forgetfulness and cognitive impairment in the last 1 year. Neuropsychological examination showed neurocognitive disturbances in orientation, attention, and visuospatial domain with impaired daily activities function. The MRI result showed subacute multiple lacunar infarctions in right insular cortex, right frontotemporal lobe cortex, right corona radiata, with multiple chronic infarcts on the right frontotemporoparietal lobe, right corona radiata, right internal genu capsule, right lateral periventricular anterior horn, pons, right left cerebellum, also senile brain atrophy. Both patients were diagnosed as VaD and given donepezil 1x10mg and memantine 1x5mg to treat the cognitive impairment. Both cases showed improvements after 6 months of therapy with MMSE from 17 to 28, MoCA-INA from 12 to 22 and MMSE from 19 to 23, MoCA-INA from 14 to 21 respectively. Discussion: The probability of acquiring vascular dementia (VaD) was strongly associated with the incidence and frequency of strokes. The prevalence of newly developed dementia after the initial stroke is approximately 10%, which increases to 30% with recurrent strokes. The likelihood of experiencing cognitive impairment and dementia after a stroke is primarily determined by the specific attributes of the stroke. While pharmacological therapy largely focuses on cognitive impairment, other factors, such as the stroke's characteristics, might contribute to neuronal and molecular abnormalities that result in cognitive loss. Two instances were shown, both demonstrating enhancements, with the initial instance, involving primary strokes, exhibiting a superior outcome compared to the subsequent instance with recurring strokes. A more profound or recurring stroke has the potential to reduce cognitive reserve, hence potentially heightening vulnerability to neurodegenerative disorders, either directly or by means of modifications in social contacts or lifestyle, which can subsequently affect cognitive performance. Conclusion: Recurrent stroke plays a role in reducing cognitive reserve and increasing the risk of dementia. Patients with VaD have shorter life expectancy, thus the severity of VaD is best managed by providing optimum acute stroke care and recurrent stroke prevention.